(3Odjd GdeOjQ aj GdNUNUIs - (3CMeO(B, (3eGgQs ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2002)
(3eGgjI GdNUNUI(B- (3bQGQ GdNUNUI(B- (3WQb GdNUNUI(B- (3GdHjY hYbhO GdEOGQI(B- (3GdNUNUI ef NdGd GdHjY ddYGedjf(B- (3Jbjje GdTQcGJ GdYGeI HZQV NUNUJgG(B- (3EYGOI gjcdI GdbWGY GdYGe(B- (3EYGOI gjcdI GdTQcI(B-(3EOGQI GdTQcGJ aj Xd GdNUNUI(B- (3GdNUNUI heTcdI GdYeGdI GdRGFOIs
Keywords: (3GdbWGY GdNGUs; (3GdbWGY GdYGes